Protean career orientation and career planning among Employees in higher education institutions in jaffna district - Aloysius, S.M.C.M.; Velnampy, T. (South Eastern University of Sri Lanka, 2020)
Protean career orientation is the individual mindset that has only fifty years of history. People have been changing slowly but steadily their career related moves to meet their career aspirations and the priorities that they have. Sri Lankan employees are in the same line in facing the changes take place in the career world. Employees develop many strategies to meet the challenges. They set career goals clearly. The present study aims to examine the effect of protean career orientation on career planning of individuals. 154 staff from public Higher Education Institutions (HEIs) participated in the study. A self-administrated questionnaire issued among the respondents. The study found that protean career orientation has significant direct impact on career planning, there is no statistically significant mean difference between men, and women in terms of their career orientation however, they are significantly different in planning their careers.
Keywords: Protean career orientation; Career goal setting; Gender; Higher education institutions